Evaluating the performance of clinical criteria for predicting mismatch repair gene mutations in Lynch syndrome: A comprehensive analysis of 3, 671 families. Issue 1 (20th February 2014) - Steinke, Verena; Holzapfel, Stefanie; Loeffler, Markus; Holinski‐Feder, Elke; Morak, Monika; Schackert, Hans K.; Görgens, Heike; Pox, Christian; Royer‐Pokora, Brigitte; von, Magnus; Büttner, Reinhard; Propping, Peter; et al.
<x xml:space="preserve">Abstract</x> Carriers of mismatch repair (MMR) gene mutations have a high lifetime risk for colorectal and endometrial cancers, as well as other malignancies. As mutation analysis to detect these patients is expensive and time‐consuming, clinical criteria and tumor‐tissue analysis are widely used as pre‐screening methods. The aim of our study was to evaluate the performance of commonly applied clinical criteria (the Amsterdam I and II Criteria, and the original and revised Bethesda Guidelines) and the results of tumor‐tissue analysis in predicting MMR gene mutations. We analyzed 3, 671 families from the German HNPCC Registry and divided them into nine mutually exclusive groups with different clinical criteria. A total of 680 families (18.5%) were found to have a pathogenic MMR gene mutation. Among all 1, 284 families with microsatellite instability‐high (MSI‐H) colorectal cancer, the overall mutation detection rate was 53.0%. Mutation frequencies and their distribution between the four MMR genes differed significantly between clinical groups (p < 0.001). The highest frequencies were found in families fulfilling the Amsterdam Criteria (46.4%). Families with loss of MSH2 expression had higher mutation detection rates (69.5%) than families with loss of MLH1 expression (43.1%). MMR mutations were found significantly more often in families with at least one MSI‐H small‐bowel cancer (p < 0.001). No MMR mutations were found among patients under 40‐years‐old with only colorectal adenoma. Familial clustering of Lynch syndrome‐related tumors, early age of onset, and familial occurrence of small‐bowel cancer were clinically relevant predictors for Lynch syndrome.